How does manufacturing agglomeration affect urban ecological resilience? evidence from the Yangtze river delta region of China - Wang, Chen (Frontiers in Environmental Science, 2024)
As rapid urbanization challenges urban ecosystem stability, understanding the relationship between manufacturing agglomeration (MA) and urban ecological resilience (UER) has become increasingly critical. This study examines how MA influences UER in China’s Yangtze River Delta region, employing dynamic spatial panel models to analyze prefecture-level panel data from 2003 to 2020. Our findings reveal an inverted U-shaped relationship between MA and UER, with significant spatial spillover effects. Specifically, moderate levels of MA enhance UER through improved resource efficiency and technological innovation, while excessive agglomeration leads to environmental degradation. The study also identifies green technological innovation as a critical mediating mechanism in this relationship. These findings contribute to theoretical understanding and policy formulation for sustainable urban development.